2000
DOI: 10.1091/mbc.11.3.1023
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Receptor Complexes on the Surface of Live Cells: A New Oligomerization Mode for Serine/Threonine Kinase Receptors

Abstract: The bone morphogenetic proteins (BMPs) play important roles in embryogenesis and normal cell growth. The BMP receptors belong to the family of serine/threonine kinase receptors, whose activation has been investigated intensively for the transforming growth factor-beta (TGF-beta) receptor subfamily. However, the interactions between the BMP receptors, the composition of the active receptor complex, and the role of the ligand in its formation have not yet been investigated and were usually assumed to follow the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
252
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(271 citation statements)
references
References 56 publications
16
252
0
1
Order By: Relevance
“…This is consistent with a recent experimental finding [18]. We have studied clustering, based on an appropriate definition of clustering correlation function.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…This is consistent with a recent experimental finding [18]. We have studied clustering, based on an appropriate definition of clustering correlation function.…”
Section: Summary and Discussionsupporting
confidence: 91%
“…Most proteins of the BMP family bind to two types of signaling receptors termed as type I and type II receptors. 52 The type II receptors are kinases, which are constitutively active without ligand stimulation. Upon ligand binding and formation of type II and type I receptor complexes, followed by possible receptor conformational changes, type I receptors are phosphorylated and activated by type II receptor kinases.…”
Section: Discussionmentioning
confidence: 99%
“…(8,9) The experimental study of BMP-2 signaling and BMP responsiveness is challenging and is complicated by at least two issues: (1) cross-talk with numerous other pathways (15,16) and (2) lack of synchronization of cellular differentiation in spontaneously differentiating heterogeneous preosteoblast cultures. (25) Several studies have demonstrated that MAPKs are required for BMP-2-induction of the osteoblastic phenotype and mineral deposition in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, R-Smads associate with Smad4 and translocate to the nucleus to regulate gene expression. (8)(9)(10) Inhibitory Smads6 and -7 potently antagonize the BMP/Smad pathway by interacting with activated BMPR-I and preventing activation of R-Smads or by competing with activated R-Smads to form complexes with Smad4. (11)(12)(13)(14) BMP responsiveness may be modulated in part by complex cross-talk with other signaling pathways, including mitogenactivated protein kinases (MAPKs).…”
Section: Introductionmentioning
confidence: 99%